DEBATING “GOLDEN LEAF”: A HISTORICAL PERSPECTIVE ON SOCIO-CULTURAL ASPECTS OF SMOKING AND TOBACCO CONTROL - Nawiyanto N (LITERASI: Indonesian Journal of Humanities, 2013)
A series of controversies have been a striking phenomenon colouring the existence of tobacco and smoking habit. Drawing upon the available and reachable source materials, mainly secondary ones, the present paper seeks to trace broadly the historical roots of opposition to tobacco and smoking and the recent development of the pro and cons concerning the two issues. A special attention is going to be paid to the arguments built by the conflicting to support their own positions. It is argued that the debates on tobacco and smoking have long taken place, parallel with their spreads from the Americas to the European Continent and the other parts of the world. The debates have been increasingly fierce, in which many parties are getting involved. The present pros and cons conflict might be simplified to certain extent into a battle of “profit versus health”, which is radically different from the earlier battle in which health considerations were initially an integral part of the explanation for tobacco and smoking expansion. In the past the moralistic arguments played a major role in the opposition against tobacco and smoking. Recently the position has been replaced by health issues, serving as the core arguments in the antismoking and tobacco movements emerging over the last couple of decades. Keywords: controversy, tobacco, smoking habit, past time, contemporary period